2010
DOI: 10.1002/cyto.b.20560
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of circulating tumor cells from a large blood volume using leukapheresis and elutriation: Proof of concept

Abstract: Background: The aim of this study was to determine the applicability of a sequential process using leukapheresis, elutriation, and fluorescence-activated cell sorting (FACS) to enrich and isolate circulating tumor cells from a large blood volume to allow further molecular analysis.Methods: Mononuclear cells were collected from 10 L of blood by leukapheresis, to which carboxyfluorescein succinimidyl ester prelabeled CaOV-3 tumor cells were spiked at a ratio of 26 to 10 6 leukocytes. Elutriation separated the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
(87 reference statements)
0
55
0
Order By: Relevance
“…Another factor that might contribute to a more reliable CTC detection by DLA is that the final LA products were generated from at least more than half of the whole circulating blood volume (cohort 2), thereby reducing the sampling error of a simple venipuncture. Eifler et al suggested by their proof-of-concept study using apheresis products spiked with cancer cell lines that an additional elutriation step might even further enhance CTC recovery after high-volume screening for CTCs by apheresis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that might contribute to a more reliable CTC detection by DLA is that the final LA products were generated from at least more than half of the whole circulating blood volume (cohort 2), thereby reducing the sampling error of a simple venipuncture. Eifler et al suggested by their proof-of-concept study using apheresis products spiked with cancer cell lines that an additional elutriation step might even further enhance CTC recovery after high-volume screening for CTCs by apheresis (21).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent conflict could be solved by in vivo detection methods, in which feasibility has been shown (48)(49)(50)(51). An alternative approach is to conduct leukapheresis for CTC isolation (52). Although this procedure is more cumbersome compared with a simple blood draw, it is more attractive than taking biopsies from the metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is the development of leukapheresis, elutriation for subsequent ex vivo CTC analyses that use flow cytometry, and real-time PCR for molecular characterization (25 ). Eifler et al showed that leukapheresis collected 13.5 ϫ 10 9 mononuclear cells with 87% efficiency.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%